Performance of silicon photomultipliers from room temperature to below 200 mK - Hanski, Otto; Kiilerich, Tom; Ahopelto, Sampsa; Semakin, Aleksei; Ahokas, Janne; Dvornichenko, Viacheslav; Vasiliev, Sergey (SPRINGER, 2026)
We present experimental results of characterization of Silicon photomultipliers (SiPM) in a temperature range from 90 mK to 40 K and compare them to room-temperature results. Two SiPMs, one from ONSEMI and one from Hamamatsu Photonics, were tested. Operating voltage ranges, dark count rates, afterpulsing effects and photon detection efficiencies (PDE) were determined with illumination by 275- and 470-nm light fed into the cryostat via an optical fiber. A cryogenic shutter provided a true dark condition, where thermal radiation from room temperature is shielded and the thermal excitations in the chips are frozen. A second tunneling breakdown was observed at this condition, which substantially limits the operating voltage range for the temperatures 20-30 K. Below ∼5 K, both SiPMs recover to an operating overvoltage range of 3-5 V. We found the chips function through the entire tested temperature range and are capable of withstanding thermal cycling with no major performance degradation.